Moje sanje - majhno stanovanje? - Černič Mali, Barbara (Urbani izziv, 1993)
The article deals with changes in the housing market in Slovenia after the new Law on Housing was accepted, especially on the secondary market, meaning housing which is not newly built. Presented are the results of a telephone survey and data of real estate agencies.
Keywords: bivalno okolje; Ljubljana; mesta; stanovanjski trg; stanovanjsko gospodarstvo